Mom's Knowledge Regarding Basic Immunization To Babies In The Sigumpar Public Health Center Area Year 2021 - Melva Epy Mardiana Manurung (Institute of Computer Science (IOCS), 2021)
Immunization is an effort to provide immunity to infants and children by introducing vaccines into the body to make antibodies to prevent certain diseases. There are 22.6 million children in the world who are not covered by routine immunization. More than 13% of Indonesian children have not received complete immunization for various reasons, whereas complete immunization can protect children from epidemics, disability and death. The percentage of measles immunization nationally is 82.1%, DPT/HB1 immunization is only 3.3%, the number of diphtheria cases is 78.4%, this achievement has not met the 90% target which is Indonesia's commitment to the regional scope. Not achieving the immunization target is caused by various things, one of which is lack of knowledge from mothers about immunization. This study aims to determine the knowledge of mothers about giving basic immunization to babies in the work area of ​​the Sigumpar Health Center, Tobasa Regency. The type of research used is descriptive, the population in this study is mothers who have babies 0-12 months and the research sample is 31 people who are taken by doing accidental sampling. The results of this study indicate that the majority of mothers' knowledge is in good category (67.7%) about giving basic immunization to babies at the Sigumpar Health Center, Tobasa Regency. direct visits so as to increase visits and maternal compliance in providing immunizations to their children so as to prevent disease for the baby's body.